A Flexible Piezoresistive/Self-Capacitive Hybrid Force and Proximity Sensor to Interface Collaborative Robots - Fonseca, Diogo (2023)
Force and proximity sensors are key in robotics, especially when applied in collaborative robots that interact physically or cognitively with humans in real unstructured environments. However, most existing sensors for use in robotics are limited by: 1) their scope, measuring single parameters/events and often requiring multiple types of sensors, 2) being expensive to manufacture, limiting their use to where they are strictly necessary and often compromising redundancy, and 3) have null or reduced physical flexibility, requiring further costs with adaptation to a variety of robot structures. This paper presents a novel mechanically flexible force and proximity hybrid sensor based on piezoresistive and self-capacitive phenomena. The sensor is inexpensive and easy to apply even on complex-shaped robot structures. The manufacturing process is described, including controlling circuits, mechanical design, and data acquisition. Experimental trials featuring the characterisation of the sensor were conducted, focusing on both force-electrical resistance and self-capacitive proximity response. The sensor's versatility, flexibility, thinness (1 mm thickness), accuracy (reduced drift) and repeatability demonstrated its applicability in several domains. Finally, the sensor was successfully applied in two distinct situations: hand guiding a robot (by touch commands), and human-robot collision avoidance (by proximity detection).